(untitled) (Research, Society and Development, 2021)
The present study refers to the transformations in aerobic dance classes that took place in the 40 years of aerobic gymnastics in Brazil. Aerobic gymnastics is characterized by rhythmic and intense movements with high caloric expenditure because it demands a lot from the person and impacts the joints, leaving the person healthier from the moment he starts exercising and creating movements. This research aimed to analyze the evolution of gym classes in the gym and its most expressive changes. As a methodology, materials will be included in the study that reveal the different types of aerobic modality according to each period, whether articles, websites, materials, or other documents. Through the analyzed results, it was verified that gymnastics was changing over the years, influenced by cultural and musical movements according to some periods. In this way, gymnastics can be easily transformed into safe, uncomplicated and rewarding for everything, and still retain the element that causes “emotion” – that kinesthetic stimulation that immediately leads students to want more. The research revealed that since its emergence in Brazil, aerobic gymnastics has gone through different periods that influenced its various methodologies and then changes, with the inclusion of Latin and Brazilian music, such as lambaeróbica, Bodysistems, zumba and most recently fitDance.